Transition metal atom–doped monolayer MoS2 in a proton-exchange membrane electrolyzer - Mo, J; Wu, S; Lau, THM; Kato, R; Suenaga, K; Wu, TS; Soo, YL; Foord, JS; Tsang, SCE (Elsevier, 2020)
There has been a substantial research effort worldwide to develop non-noble metal catalysts for H2 production from water splitting using renewable energy sources, but most data were evaluated by voltammetry in laboratories. Here, exposed basal planes of MoS2 monolayer nanosheets with metal dopants across the first transition metal (TM) series in the periodic table (Fe, Co, Ni, Cu) are used as cathode catalysts for the proton-exchange membrane (PEM) water splitting in an electrolyzer under typical conditions of strong acidity with more negative applied voltage. Extended X-ray absorption fine structure spectroscopy (EXAFS) analysis and high-angle annular dark-field scanning transmission electron microscopy (HAADF–STEM) images show a direct proof on the single TM atoms residing at the surface basal sites, which subtly modify the electrocatalytic activity of the monolayer MoS2, depending on their electronic and metal-hydrogen binding ability. We report that Co-sMoS2 yields the highest current density in an electrolyzer with the hydrogen evolution reaction (HER) activity comparable with that of the commercial 20 wt% Pt/C under industrial applicable conditions. A general trend for the other TMs has also been established as evidenced by the change in TM effective nuclear charge across the periodic table, which perturbed the TM-Mo interaction and hence affects the HER activity.